Together we stand? Transnational solidarity in the EU in times of crises. (March 2022) - Katsanidou, Alexia; Reinl, Ann-Kathrin; Eder, Christina
After more than a decade of consecutive crises, the issue of transnational solidarity is becoming increasingly relevant for the European Union. This research note compares the current coronavirus disease-2019 crisis to previous ones and investigates the willingness of European Union citizens to show solidarity towards fellow member states. We test the influence of socio-political attitudes of citizens on solidarity preferences in three crisis scenarios. We analyse Greece and Germany as cases differently affected by the past decade's crises and cases that chose different crisis management strategies when facing the novel virus. Our findings indicate that solidarity is highest in a pandemic, while for all crisis scenarios it is higher in Greece than in Germany. Despite variations in the degree of solidarity associated relationships with socio-political attitudes remain consistent.